Laserstrahlschmelzabtrag - Prozessanalyse und -modellierung - Cser, Adrienn Orsolya (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2005)
Despite of its numerous advantages laser beam melt ablation is, due to the lack of process understanding, still not generally accepted by the industry today. Through the analyses performed in this work substantial new insights could be won. The possibility of process control and on-line surveillance was created, and the direction for the improvement of surface quality and process optimization through laser power modulation was pointed ou